Min Asrār al-‘Udūl fī Siyag al-Asmā’: One of the Secrets of Modulation in Noun Forms - Sulaima, Raziyu Lawal; Haruna, Haruna Abubakar (Study Program of Arabic Language Teaching, 2023)
Changing from the form of the pronunciation to another form only occurs due to a specificity necessitated by the context, and is not envisaged in the speech of the Arabs except by those who know the symbols of eloquence, eloquence, and meanings, and know the secrets of the speech of the Arabs. Variation in the morphological forms of nouns of all kinds is also not an obstacle, especially in Quranic expression, but rather leaves a semantic guide required by the context, occasions, and positions. Among these connotations is the departure from the original meaning to a secondary meaning or another meaning through which it indicates an additional meaning, such as changing from the infinitive to the plural and vice versa, from the masculine to the feminine and vice versa, from the indefinite to the definite article, from the infinitive to the derivatives and vice versa, and so on. This paper aims to reveal those connotations and rhetorical meanings behind the phenomenon of variation in the forms of nouns according to morphological rules and sometimes syntactic, while pointing out some of the differences in opinions of scholars on the issue in which these differences were found.